THE EFFECTIVENESS OF AI IN ENHANCING THE PEOPLE’S ECONOMY TO ACHIVE INDONESIA EMAS 2045 - Ajeng Nisa Kusuma; Kunto Arief Wibowo; Shafa Dhia Raharja (Multifinance, 2025)
To be able to get to a Golden Indonesia in 2045 is not an easy thing, it is actually a challenge for the Indonesian people. Golden Indonesia 2045 has a pillar, one of which is a sustainable economy. In a sustainable economy, it can be implemented through a people's economy whose values of the people's economy here refer to the family economic system, and can build MSMEs for Indonesia, so that the people's economy here can be a driver to implement a Golden Indonesia in 2045. In this study, it is also associated with AI as artificial intelligence that can actually provide an innovation for its users, not only that, but AI can also help the people's economy here to be implemented easily. In this study, it raises the effectiveness of AI in improving the people's economy in order to be able to move towards a Golden Indonesia 2045. The results of this study actually look at two sides, the first is that AI can effectively improve the people's economy, but on the one hand it can actually have a negative impact on economic actors, and later it can refer to the people's economy in realizing a Golden Indonesia 2045.